Composite Nanostructure Construction on the Grain Surface of Li‐Rich Layered Oxides. Issue 49 (5th November 2020) - Wang, Errui; Zhao, Yang; Xiao, Dongdong; Zhang, Xu; Wu, Tianhao; Wang, Boya; Zubair, Muhammad; Li, Yuqiang; Sun, Xueliang; Yu, Haijun
Abstract: Li‐rich layered oxides (LLOs) are fascinating high‐energy cathodes for lithium‐ion batteries (LIBs), but still suffer from critical drawbacks that retard their practical applications. Although surface modification is effective to protect LLOs from structural deterioration, the delicate design of structures on a grain surface with promising scalability for industrial application is still challenging. Herein, using the atomic layer deposition (ALD) technique, a composite nanostructure comprising a uniform LiTaO3 coating layer (≈3 nm) and a spinel interlayer structure (≈1 nm) is constructed on the grain surface of industrial LLO (Li1.13 Mn0.517 Ni0.256 Co0.097 O2 ) agglomerated spheres. The surface composite nanostructure can not only enhance the structural/interfacial stability of the LLO, but also facilitates Li + diffusion, thereby significantly improving its cycle stability, rate performance, thermal stability, and voltage maintenance. Specifically, the LLO coated with 10 ALD cycles exhibits a small voltage decay rate of 0.9 mV per cycle, a reversible capacity of 272.8 mAh g −1 at 0.1 C, and a capacity retention of 85% after 200 cycles at 1 C, suggesting the important role of surface composite nanostructure for improving the electrochemical performance. This work provides new insights into the composite nanostructure design on the grain surface of cathode materials for high‐performance LIBs. Abstract : A composite nanostructure comprising a uniform LiTaO3 coating layer and the oriented growth of a spinel interlayer structure is constructed on the grain surface of Li‐rich layered oxides (LLOs) by the atomic layer deposition (ALD) technique. The surface composite nanostructure modification can significantly improve the voltage maintenance, cycle stability, rate performance, and thermal stability of LLOs.